Developing Gender and Youth-Responsive Agronomic Solutions for Use Cases in the Excellence in Agronomy Initiative: Standard Operating Procedure - Cole, Steven Michael; Lambrecht, Isabel B.; Iradukunda, Francois (2023)
This Standard Operating Procedure (SOP) is designed for Excellence in Agronomy (EiA) Use Case teams with an interest in developing gender- and youth-responsive agronomic solutions. The SOP is a guide to help Use Case teams move from each step in their workflows when designing, validating, and piloting their Minimum Viable Products (MVPs) to ensure they can develop gender- and youth-responsive agronomic solutions by the end of their Use Case. This stepwise procedure first entails carrying out a diagnostic assessment of gender and generational differences in agricultural management practices and technology adoption and the factors contributing to these differences. The evidence generated is utilized by Use Case teams to inform the design of their MVPs to ensure they are responsive to the diverse needs and circumstances of especially women and youth smallholder farmers in their focal context. The design phase also considers the extension support approach needed for use when validating and piloting MVPs. During both these stages, Use Case teams collect additional information to determine whether the MVPs are meeting the needs of women, men, and youth, and adjust accordingly before the MVP can be taken to scale by partners. These steps (6 total) to developing gender- and youth-responsive agronomic solutions are described with some detail in this SOP. See Figure 1 for an overview of the stepwise procedure.